2017
DOI: 10.1002/rcr2.248
|View full text |Cite
|
Sign up to set email alerts
|

An intimal sarcoma of pulmonary artery mimicking pulmonary embolism: a case report and literature review

Abstract: Pulmonary artery intimal sarcoma is a highly aggressive disease, and is most often misdiagnosed as pulmonary thromboembolism (PTE) due to the similar clinical symptoms and its rarity, which leads to the use of inappropriate treatments such as prolonged anticoagulant therapy. We reported a case of pulmonary artery intimal sarcoma in a patient who was misdiagnosed as having PTE. Pathology after surgery confirmed malignant disease. We concluded that when a patient presents with mild clinical manifestations yet wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The impact of chemotherapy and radiotherapy in PAIS remains unclear, although some studies have demonstrated that these therapies prolong survival after surgical treatment. 3,4 Our patient underwent chemotherapy with paclitaxel. Because early and proper diagnosis is necessary for appropriate therapy, clinicians should consider the possibility of PAIS even if imaging findings are inconsistent with the disease.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The impact of chemotherapy and radiotherapy in PAIS remains unclear, although some studies have demonstrated that these therapies prolong survival after surgical treatment. 3,4 Our patient underwent chemotherapy with paclitaxel. Because early and proper diagnosis is necessary for appropriate therapy, clinicians should consider the possibility of PAIS even if imaging findings are inconsistent with the disease.…”
Section: Discussionmentioning
confidence: 97%
“…PAIS is often misdiagnosed as PTE. [2][3][4][5] PAIS has a poor prognosis due to delayed diagnosis and distal spread of the disease, with survival outcomes of 36.5 AE 20.2 and 11 AE 3 months for patients having curative resection and incomplete resection, respectively. 4 CT findings differentiating PAIS from PTE include hyperdense lesions with nonhomogeneous attenuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 PAS appears as a delayed contrast enhancement on CT angiography scans, more evident in the venous phase. 21,24,25 The presence of multiple lung nodules can raise a suspicion for a malignancy like PAS. 19…”
Section: Introductionmentioning
confidence: 99%
“…25 Reported surgical treatments include lobectomy or pneumonectomy for unilateral cases, pulmonary endarterectomy, and tumor debulking with or without graft reconstruction of the pulmonary artery for bilateral cases. 23,25,29 The goal of pulmonary endarterectomy is to relieve the obstruction caused by the tumor, which causes significant improvement in symptoms but this is not curative. 23 The role of chemotherapy and radiation post-surgery is yet unclear.…”
Section: Introductionmentioning
confidence: 99%